Particle damping-based design for vibration and noise reduction of interior wooden flooring in high-speed railway trains - TANG Yanning; DAI Yu; XIAO Wangqiang; SHAO Kun (机车电传动)
With the continuously increasing speeds of high-speed trains, the impacts of vibration and noise have become more significant. Consequently, there is an escalating demand for enhanced sound insulation performance and lighter design of interior wooden flooring in high-speed trains. This paper presented a design aimed at improving the sound insulation performance of interior wooden flooring with specific sizes. The design process initially involved the appearance and structure of particle dampers for the interior wooden flooring. The approach utilized the discrete element method to meet the installation requirements. Subsequently, an investigation was conducted into the sound insulation effects of various factors on the interior wooden flooring, including installation areas, particle materials, and particle sizes, through the calculations of energy consumption values for different particle damper configurations. This step identified an optimal configuration option. Finally, sound insulation tests were conducted to verify the effectiveness of the chosen option. The experimental data show the consistency between the sound insulation performance under different particle damper configurations and the discrete element simulation results, thereby demonstrating the effectiveness of the discrete element model. Moreover, the optimal particle damper configuration yields a significant improvement in sound insulation across all frequency bands, resulting in a weighted sound insulation increase of 3.9 dB. This result successfully achieves the desired goal and substantiates the efficacy of the particle damper in reducing vibration and noise in interior wooden flooring. The application of particle damping technology to address vibration and noise reduction in interior wooden flooring of high-speed trains provides a novel idea for vibration and noise reduction in structures similar to the interior flooring of high-speed trains, which has both important engineering significance and application value.